The present and the future of Greek consumption patterns - Μαντζουνέας Ηλίας; Στοφόρος Χρυσόστομος (SPOUDAI Journal of Economics and Business, 2003)
The estimation of demand response parameters is important for determining policy-oriented strategies for both the public and the private sectors of the economy since private consumption amounts a large proportion of GDP. Thus, it is a necessity to develop a methodology in order to forecast trends and changes in consumption patterns given some alternative scenarios based on future evolution of private expenditure. In this paper a coherent methodology is presented for estimating and forecasting consumption patterns with an application to Greek economy. The results include both price and expenditure elasticities as well as the future trends (2001-2010) of the shares of the main consumption aggregates in total consumption expenditure. The main conclusion is that Greek consumers will tend to decrease their expenditure share on necessities and increase consumption of luxuries as their real disposable income increases but with a relatively slow pace. The main aggregates that will be benefited by these changes are Clothing - Footwear, Furnishings - Household Equipment - Routine Maintenance of the House, Transportation - Communication, Health and Recreation - Culture. Finally, Food - Beverages - Tobacco is the category that will have the strongest negative trend over the 2001-2010 period. JEL: Classification: D12, C32